The use of face-threatening acts in the construction of in- and out-group identities in British parliamentary debates - Mollin, Sandra (The discursive construction of identities on- and offline, 2018)
Identity construction is group membership construction in that humans bring their individual selves into being by declaring and performing their belonging to in-groups which are constructed in contrast to out-groups, as suggested in Tajfel’s theory of social identity. In parliamentary discourse, the establishment and reinforcement of in- and out-group identities is particularly important, since parliamentary discourse represents an institutionalized arguing game of ‘us’ versus ‘them’ (between political parties). One decisive way in which these group identities are construed and maintained is through the use of face-threatening acts (FTAs), analyzed here in British House of Commons debates on health policy. A taxonomy of FTAs in this context is developed, allowing for an analysis of addressers and addressees, and close interpretation of examples leads to the conclusion that FTAs are used to denigrate the out-group and strengthen in-group identification at the same time.